PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA KELAS IV SD NEGERI BIBIS - Arel Sabila, Thifan; Purnomo, Heru (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the effect of the use of learning media on student learning achievement. This study uses a quantitative approach with an experimental method and a one-shot case study design, where the effect of the use of learning media is tested after one treatment. The study population included 25 grade IV A students, while the sample was determined randomly using a random sampling technique. The data were analyzed using a paired sample t-test to see the difference in student achievement before and after treatment. The results showed that the use of learning media had a significant effect on improving student learning achievement, with a significance value (Sig. 2-tailed) <0.000, which is smaller than the significance limit of 0.05. Thus, it can be concluded that learning media effectively helps improve student achievement, showing a strong relationship between its use and learning outcomes. This study provides empirical evidence of the importance of innovation in teaching methods to improve the quality of education.